Impact of Financing on Small and Medium Enterprises (SMEs) Profitability with Moderating Role of Islamic Finance - Muneer, Saqib; Ali, azhar; Ahmad, Rao Abrar (Information Management and Business Review, 2017)
Small and medium enterprises (SMEs) are the very significant for the development of economy of the country, grasp the attention of government and policy makers in developed as well as in developing countries. SMEs in Pakistan have their vital role in economic growth. Therefore, it is essential that SMEs have right to use sources of finance. The study used the quantitative approach that was accomplished by survey questionnaires. Two hundred SMEs and seventy bank branches were selected in Faisalabad region in Pakistan, to get response on questionnaires about their financing patterns and effects of Islamic financing as moderator in their fixed assets, set up and current assets financing. The study showed that fixed assets, set up and current asset financing have positive relation with the growth of SMEs and Islamic modes of financing was not behaved as moderator in Faisalabad city in Pakistan.